Making photography matter : a viewer's history from the Civil War to the Great Depression - Finnegan, Cara A. (University of Illinois Press, 2015)
The presence of unknown soldiers and imaginary spirits : viewing national grief and trauma in the Civil War -- Recognizing Lincoln : portrait photography and the physiognomy of national character -- Appropriating the healthy child : the child that toileth not and Progressive Era child labor photography -- Managing the magnitude of the Great Depression : viewers respond to FSA photography.